KAWASAN LINDUNG GUNUNG CIREMAI DAN KEMUNGKINAN PENGELOLAANNYA - Noerdjito, Mas; Mawardi, Sonny (Perhimpunan Biologi Indonesia, 2008)
ABSTRACTProtected Area and Conservation Strategy of Ciremai Mountain. The Ciremai MountainWest Jawa as one of the important water catchments area and as water supplier area forMajalengka, Kuningan, Cirebon, Indramayu district in West Jawa provice and part of Brebesdistrict in Central Jawa Province. In order to uphold its function in storing water resources, itis important to understand the protected area of Ceremai Mountain. The protected area wasestablished on its altitude, elevation, and type of soil of about 22,600 ha. 15,410 ha or 68.20%of this area has been recovered, including 8,320 ha of Ceremai Mountain National Park.Reforestation of the ex-pinus area was necessary to increase water reservation. Besides thatCeremai Mountain National Park was needed to be managed with agro forestry.Keywords: protected area, Ciremai, storing water resources